Synthesis and characterization of composite film based on cellulose of napier grass incorporated with chitosan and gelatine for packaging material - Tuan Rohadi, T. N.; Ridzuan, M. J.M.; Abdul Majid, M. S.; Azizan, A.; Mat, Fauziah; Sapuan, S. M. (Springer, 2023)
Mitigating environmental pollution, which adversely affects humans, wildlife, and habitat, has been attracting increasing attention worldwide, especially with reference to the importance of using composite films. In this study, composite films consisting of cellulose, chitosan, and gelatine were analysed and characterized. It was fabricated via a solution casting method. The cellulose extracted from the whole stem, cortex, and pith of Napier grass with 4, 8, 12, and 16% alkali concentrations were used to produce the composite films. Based on the thermogravimetric analysis, mechanical analysis, Fourier-transform infrared spectroscopy (FTIR) analysis, X-ray diffraction (XRD) analysis, and scanning electron microscopy (SEM) observation, it was confirmed that the interaction of cellulose of Napier grass, chitosan and gelatine had improve the thermal behaviour, strength, composition, crystallinity, and morphology of composite films. The composite films using 8% alkali-treated cellulose from the whole stem had an ordered structure with 2θ = 22.68°. Furthermore, it contained the highest final residue (74.85%) and tensile strength of 4.58 ± 0.373 MPa.